A Comparison Study of Garlic and Propolis Extract as Biological Activity on Staphylococcus aureus Isolated from Diabetic Foot Patients - Ghazal, Sabreen G.; Gihad , Zeena Kareem; Saad, Hanan (Medical Science Journal for Advance Research, 2024)
Background: Plant extracts play a crucial role in biological activity in recent years the extraction of some active material from some plants indicates good activity challenging the excess types of bacteria without side effects. Methods: Simple extraction is used to extract garlic using water as a solvent and ethanol for propolis. the Garlic and Propolis extract used on the Staphylococcus aureus which was isolated and identified from diabetic foot patients after culturing the bacteria on Mullar Hinton media the biological activity was measured for the Garlic and Propolis extract. Results: The elevated concentration of the garlic extracts (C) produced elevated inhibition by S. aureus (32 mm); the smallest inhibition zone was detected by Staphylococcus aureus (19 mm) in the minimal concentration of the garlic extracts. While the elevated concentration of the propolis extracts produced the elevated inhibition zone by S. aureus (20mm), the smallest inhibition zone (14mm) was detected by Staphylococcus aureus in the low concentration of propolis extract. The inhibition zone of the garlic extracts (at 5% concentration) was the larger than the propolis extract at 5gagainst S. aureus (32 vs 20 mm). The MIC method by S. aureus of the garlic extract resulted 12.5 mg/ml, while, the propolis extract resulted 3.2 mg/ml. The MBC recognized by the lack the growth of the tested bacteria that inoculated from the inhibition well initial from the maximum concentration (100 mg/ml) reached to the concentration equivalent the minimal MIC. The garlic extract exhibited an absence growth of bacteria for total inoculation which confirmations potentially bactericidal action to S. aureus have an MBC at 12.5 mg/ml. Conclusion: The elevated concentration of the garlic extracts produced the elevated inhibition towards S. aureus as well as the least inhibition zone detected in the minimal concentration of the garlic extracts towards Staphylococcus aureus. Whatever the concentration of the garlic extracts used in the present study, the inhibition zone was larger as compared with propolis. The results indicate that the garlic extract was more active than the propolis extract. The results prove the efficiency of garlic extract, which makes them suitable for medical treatment used as an ointment form or tablet to treat ulcers suffered by patients with chronic diabetes.